2020
DOI: 10.1080/14756366.2020.1835885
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pesticides on honey bee carbonic anhydrase inhibition

Abstract: Carbonic anhydrase (CA, EC 4.2.1.1) plays crucial physiological roles in many different organisms, such as in pH regulation, ion transport, and metabolic processes. CA was isolated from the European bee Apis mellifera (AmCA) spermatheca and inhibitory effects of pesticides belonging to various classes, such as carbamates, thiophosphates, and pyrethroids, were investigated herein. The inhibitory effects of methomyl, oxamyl, deltamethrin, cypermethrin, dichlorodiphenyltrichloroethane (DDT) and diazinon on AmCA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The carbamates and organophosphates investigated here possess ester bonds, which can be hydrolysed by the esterase activity of the a‐CAs. In fact, it has been thoroughly documented that these enzymes are esterases/thioesterases/selenoestearses with carboxylic, phosphoric, thiocarboxylic, and even selenol esters 53 . It was reported that carbamates bind to the CA active site through their deprotonate carbamate nitrogen, which coordinates the catalytic metal ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbamates and organophosphates investigated here possess ester bonds, which can be hydrolysed by the esterase activity of the a‐CAs. In fact, it has been thoroughly documented that these enzymes are esterases/thioesterases/selenoestearses with carboxylic, phosphoric, thiocarboxylic, and even selenol esters 53 . It was reported that carbamates bind to the CA active site through their deprotonate carbamate nitrogen, which coordinates the catalytic metal ion.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been thoroughly documented that these enzymes are esterases/thioesterases/selenoestearses with carboxylic, phosphoric, thiocarboxylic, and even selenol esters. 53 It was reported that carbamates bind to the CA active site through their deprotonate carbamate nitrogen, which coordinates the catalytic metal ion. In this study, X-ray crystallography of the CA-carbamate interaction showed the direct binding of these compounds to a metal ion.…”
Section: μM)mentioning
confidence: 99%
“…It is involved in diverse and important processes in insects, such as aging and longevity, insecticide susceptibility, food intake, and courtship [ 44 , 45 , 46 ]. Carbonic anhydrases are involved in pH regulation, ion transport, metabolic processes, and insecticides resistance [ 47 , 48 ]. In insects, nose resistant to fluoxetine protein has only been characterized in the fruit fly, Drosophila melanogaster , which participates in oogenesis and embryogenesis and neurodegeneration [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%